Analisis Kemampuan Literasi Matematika Siswa Sekolah Dasar - Andrian, Firma; Tusriyanto, Tusriyanto; Rahmawati, Ratih (Tapis: Jurnal Penelitian Ilmiah, 2022)
It is necessary to develop students' mathematical literacy skills from an early age, starting from elementary school considering that the results of Indonesian students' mathematical literacy in the 2018 PISA assessment are very concerning, where Indonesian students are ranked 6th lowest. The purpose of this study was to analyze the extent of elementary school students' mathematical literacy skills. The research method used is descriptive qualitative. The research subjects were fifth grade students of SD IT Wahdatul Ummah Metro Lampung City with high, medium and low levels of students' mathematical abilities. Data collection techniques using test methods, interviews and documentation. Data were analyzed by triangulation technique. The results of the study showed that students who had high mathematical abilities were able to solve mathematical literacy questions correctly up to level 3 only, for questions at levels 4 to 6 they only met the indicators of formulate mathematical process. Students with medium and low literacy skills are only able to solve math literacy questions up to level 2, students with moderate abilities are unable to fulfill the mathematical process indicators on questions level 4 to 5, but for level 6 questions students with moderate ability fulfill the indicators of formulate mathematical process. Meanwhile, students with low abilities did not meet the indicators of mathematical literacy levels 4 to 6 at all.